2016
DOI: 10.4028/www.scientific.net/kem.724.48
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Diffusion Processes in AlAs/GaAs Resonant-Tunneling Heterostructures

Abstract: The problem of reliability prediction and assurance is characteristic of wireless devices based on nanoscale multilayer heterostructures because of the sensitivity of heterostructures’ parameters to the degradation processes due to the thinness of layers. In the current work, the degradation of the nanoscale AlAs/GaAs resonant-tunneling heterostructures due to the diffusion of the constituent elements was investigated. Analysis and comparison of data on Al and Si diffusion coefficients in GaAs shows that they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The described methodology was developed on the example of micro-and nanoelectronics devices -SHF radio signals mixer and rectifier, in which the resonanttunnelling diode (RTD) was used as a nonlinear element. The methodical basis was the results of the research of the RTD degradation processes under the influence of temperature factor and ionizing radiation, carried out by the authors [8][9][10][11][12], and the RTD diagnostic model based on these results [13][14].…”
Section: Main Partmentioning
confidence: 99%
“…The described methodology was developed on the example of micro-and nanoelectronics devices -SHF radio signals mixer and rectifier, in which the resonanttunnelling diode (RTD) was used as a nonlinear element. The methodical basis was the results of the research of the RTD degradation processes under the influence of temperature factor and ionizing radiation, carried out by the authors [8][9][10][11][12], and the RTD diagnostic model based on these results [13][14].…”
Section: Main Partmentioning
confidence: 99%
“…A number of works are devoted to the reliability of RTD and nonlinear radiosignal transmitters on its basis where reliability of RTD is studied based on the research of RTD heterostructure thermal destruction processes due to elemental interdiffusion [6,7]. It was shown, how degradation processes impact on the IV curve shape of RTD and the parameters of the radiosignal mixers based on RTD.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the RTD parameter kinetic studies under the influence of the elevated temperature are shown in [13][14][15][16].…”
Section: Reliability-prediction Technique Of Nanocomponent and Devicementioning
confidence: 99%